Post quantum cryptographic constructions - Li, Zhe (Nanyang Technological University, 2021)
With the past and ongoing developments of quantum computers, the existing asymmetric schemes are no longer secure. In a report of 2006, the National Institute of Standards and Technology (NIST) predicts that large scale quantum computers will be built within three decades. Thus, we need to actively find quantum resistant cryptographic constructions. To date, there are many proposals based on different hard mathematical problems. This thesis seeks to enrich the diversity of the quantum resistant schemes and improve the efficiency of existing schemes. We present constructions from coding theory, lattices and subset sum problems. Concretely, our quantum-safe contributions are listed as follows.